2017
DOI: 10.1002/bmc.4119
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic component profiling and identification of different Uncaria species based on high‐performance liquid chromatography–photodiode array detection tandem ion trap and time of flight mass spectrometry coupled with rDNA ITS sequence

Abstract: Uncaria is a multi-source herb and its species identification has become a bottleneck in quality control. To study the identification method of different Uncaria species herbs through HPLC-MS coupled with rDNA Internal Transcribed Spacer (rDNA ITS) sequence, both plant morphological traits and molecular identification were used to determine the species of every collected Uncaria herb. The genetic analysis of different Uncaria species was performed using their rDNA ITS sequence as a molecular marker. Meanwhile,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Nucleotide comparison of consensus sequences is a reliable method that may be considered to identify closely-related, adulterated or misidentified Uncaria species, and be used to confirm morphological and chemical identification (Zhao et al. 2018 ). For example, when a query sequence was aligned to a consensus sequence of Uncaria rhynchophylloides F.C.How, a match of six sites (118 bp-C, 152 bp-G, 247 bp-A, 447 bp-T, 493 bp-T and 580 bp-C) identified the query sequence as U. sinensis .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nucleotide comparison of consensus sequences is a reliable method that may be considered to identify closely-related, adulterated or misidentified Uncaria species, and be used to confirm morphological and chemical identification (Zhao et al. 2018 ). For example, when a query sequence was aligned to a consensus sequence of Uncaria rhynchophylloides F.C.How, a match of six sites (118 bp-C, 152 bp-G, 247 bp-A, 447 bp-T, 493 bp-T and 580 bp-C) identified the query sequence as U. sinensis .…”
Section: Resultsmentioning
confidence: 99%
“…Zhao et al. ( 2018 ) demonstrated that the liquid chromatography–mass spectrometry tandem ion trap-time of flight mass spectrometry (LCMS-IT-TOF) was a feasible method to solve the confusion in Uncaria species. Tang et al.…”
Section: Introductionmentioning
confidence: 99%
“…Another example is Uncariae Ramulus cum Uncis, EP states that its botanical source is Uncaria rhynchophylla , but there are five botanical sources in ChP: Uncaria rhynchophylla , Uncaria macrophylla , Uncaria hirsute , Uncaria sinensis and Uncaria sessilifructus . The genetic analysis based on rDNA ITS sequences showed that Uncaria rhynchophylla , Uncaria sinensis and Uncaria hirsute were closely related to each other but were far away from Uncaria macrophylla and Uncaria sessilifructus [ 14 ]. The chromatographic fingerprint showed that significant difference could be observed among the five Uncaria species, yet there were also some similarities between each other [ 14 , 15 ].…”
Section: Comparison Of Tcm Monographs Between Ep and Chpmentioning
confidence: 99%
“…The genetic analysis based on rDNA ITS sequences showed that Uncaria rhynchophylla , Uncaria sinensis and Uncaria hirsute were closely related to each other but were far away from Uncaria macrophylla and Uncaria sessilifructus [ 14 ]. The chromatographic fingerprint showed that significant difference could be observed among the five Uncaria species, yet there were also some similarities between each other [ 14 , 15 ]. As mentioned above, there are reasons to include several species and subspecies for one TCM in the monographs, but it brings more difficulty and challenges for the quality control and pharmacological study.…”
Section: Comparison Of Tcm Monographs Between Ep and Chpmentioning
confidence: 99%
“…Flavonoids display characteristic UV absorptions at 220-280 (band II) and 300-400 (band I) nm, by which they can be easily characterized [33]. Peaks 4 and 8 with UV maximum absorption at 280 nm were designated with the molecular formula of C 30 indicating flavonoids dimers.…”
Section: Flavonoidsmentioning
confidence: 99%